Indigenous Filipino Students’ Challenges, Coping Strategies, and Recommendations in Higher Education - Gaite, Cristo Rey (Journal of Interdisciplinary Perspectives, 2025)
Indigenous Peoples worldwide face persistent challenges in accessing equitable and culturally responsive education, and the Philippines is no exception. This study delves into the educational experiences of Indigenous Filipino students in higher education, examining their challenges, coping strategies, and recommendations for improvement. Drawing on qualitative case study methods and Indigenous Standpoint Theory, the research reveals the complex interplay of factors shaping Indigenous students' educational trajectories. The findings highlight the resilience of Indigenous students in adapting to the university environment and finding acceptance for their cultural identity. Despite positive experiences, challenges persist, including academic adjustment difficulties, financial constraints, and issues of discrimination and cultural identity. Indigenous students employ coping strategies such as maintaining a positive attitude and seeking support from peers. Participants offer recommendations for supporting Indigenous students, including establishing dedicated support organizations, expanding financial assistance, and promoting cultural awareness. By prioritizing Indigenous voices and perspectives, higher education institutions can create more inclusive and supportive environments, contributing to the broader goal of advancing Indigenous education and promoting social justice and equality.